2021
DOI: 10.1101/2021.02.10.430670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relation of inflammatory marker trajectories with frailty and aging in a 20-year longitudinal study

Abstract: Little is known about the development of low-grade inflammation with age and its relationship with the onset of frailty. In this exploratory study, we investigated 18 inflammatory markers measured in blood of 148 individuals aged 65-75 years at study endpoint, collected over 20 years at five-year intervals. IFNγ- and platelet activation markers changed in synchrony over time. Chronically elevated levels of IL-6-related markers, such as CRP and sIL-6R, were associated with frailty and becoming frail over time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
6
1
Order By: Relevance
“…Serum IL-6 and were undetectable in most centenarians. This finding contrasts with most of the literature that supports an increase in inflammatory markers with age [8,15,17,18,30,[33][34][35]. Additionally, serum cytokine (IL-6 and TNF-α) and CRP levels did not show association with frailty, or any other clinical feature, probably due to the fact that most centenarians had cytokine levels under the detection limit.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Serum IL-6 and were undetectable in most centenarians. This finding contrasts with most of the literature that supports an increase in inflammatory markers with age [8,15,17,18,30,[33][34][35]. Additionally, serum cytokine (IL-6 and TNF-α) and CRP levels did not show association with frailty, or any other clinical feature, probably due to the fact that most centenarians had cytokine levels under the detection limit.…”
Section: Discussioncontrasting
confidence: 97%
“…Cao and colleagues described that pre-frail subjects showed higher proportion of differentiated memory phenotypes and lower proportion of naive subsets in the CD8+ compartment, when compared to robust elder persons [14]. Frailty indexes have been vastly used as a tool to predict morbidity and mortality in the elderly [16, 34, 35]. The lower concentrations of total protein and iron levels found in frail centenarians were an expected result since hypoproteinemia and anemia are closely related to sarcopenia and frailty [33, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly within the older adult population there are differences in monocyte number and function depending on the level of frailty. It has been observed that there is an increased overall number of monocytes in frail older adults as compared to those les frail older adults (139). Classical monocytes isolated from frail older adults had increased inflammatory associated genes in response to LPS as compared to non-frail older adults (140).…”
Section: Inflammatory Cytokine Productionmentioning
confidence: 99%
“…During each measurement round, plasma samples were taken and information regarding the participants' health was collected. The present analysis is based on a sample of 16 men and 18 women who were 65-75 years of age, selected from a subgroup of DCS participants in which we previously analyzed in ammatory marker trajectories (43). The latter were still active in the DCS at least until 2016, had at least 5 plasma samples available from previous rounds, were CMV seronegative at last measurement, and did not use immunosuppressants.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify low-grade in ammation, we measured a panel of ammatory markers in 5 repeated blood samples per individual that were withdrawn at 5-year intervals over the period of approximately 20 years; details are described elsewhere (43). The panel consists of the following cytokines, chemokines and soluble receptors: C-C Motif Chemokine Ligand (CCL) 1/I-309, CCL2/MCP-1, CCL5/RANTES, CCL11/Eotaxin, CCL27/C-TACK, C-X-C Motif Chemokine Ligand (CXCL) 9 /MIG, CXCL10/IP-10, CXCL11/I-TAC, IL-10, IL-6, soluble CD40 ligand (sCD40L), soluble CD14 (sCD14), soluble IL-6 receptor (sIL-6R), glycoprotein 130 (GP130), Complement 5a (C5a), Brain-derived neurotrophic factor (BDNF), and soluble P-selectin.…”
Section: Plasma In Ammatory Protein Trajectoriesmentioning
confidence: 99%